2018
DOI: 10.1055/a-0590-5223
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Biochemometrics and Molecular Networking to Identify Antimicrobials in Angelica keiskei

Abstract: Botanical medicines have been utilized for centuries, but it remains challenging to identify bioactive constituents from complex botanical extracts. Bioassay-guided fractionation is often biased towards abundant or easily-isolatable compounds. To comprehensively evaluate active botanical mixtures, methods that allow for the prioritization of active compounds are needed. To this end, a method integrating bioassay-guided fractionation, biochemometric selectivity ratio analysis, and molecular networking was devis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 29 publications
(43 reference statements)
0
38
0
2
Order By: Relevance
“…159 This study found that data transformation, contaminant filtering, and model simplification tools had major impacts on the selectivity ratio models, emphasizing the importance of proper data processing approaches for extracting reliable information from biochemometric datasets. 159 In all selectivity ratio studies applied to identify bioactive natural products, 146,159,160 bioactive mixture constituents were identified early in the fractionation process, enabling chromatographic isolation efforts to be tailored to mixture constituents that were most likely to possess bioactivity.…”
Section: Identifying Constituents Responsible For Combination Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…159 This study found that data transformation, contaminant filtering, and model simplification tools had major impacts on the selectivity ratio models, emphasizing the importance of proper data processing approaches for extracting reliable information from biochemometric datasets. 159 In all selectivity ratio studies applied to identify bioactive natural products, 146,159,160 bioactive mixture constituents were identified early in the fractionation process, enabling chromatographic isolation efforts to be tailored to mixture constituents that were most likely to possess bioactivity.…”
Section: Identifying Constituents Responsible For Combination Effectsmentioning
confidence: 99%
“…(Apiaceae) and the molecular families to which they belonged. 160 Using this approach, a subset of chalcone analogs were targeted for isolation, yielding two known antimicrobial constituents and an additional, low-abundance compound not previously known to possess antimicrobial activity. 160 This concept was streamlined into a process called “bioactive molecular networking,” in which bioactivity predictions are directly visualized in molecular networks themselves, where the size of individual nodes correspond to the predicted bioactivity score for each ion (Fig.…”
Section: Identifying Constituents Responsible For Combination Effectsmentioning
confidence: 99%
“…[162][163][164] PLS modeling has been adapted to identify individual (or several) metabolites that are predicted to be responsible for the bioactivity of a complex natural product mixture. 77,165,166 For the NaPDI Center study of green tea, a biochemometric approach was used to predict which catechins were responsible for the in vitro inhibition of intestinal UDP-glucuronosyltransferases (UGTs). The selectivity ratio [167][168][169] was used as a metric to demonstrate the extent to which a given mixture constituent was associated with biological activity.…”
Section: Determining Which Constituents Of a Botanical Natural Producmentioning
confidence: 99%
“…23 XAG, an active constituent isolated from the Japanese koidzumi (Ashitaba) herb, has recently attracted attention for its extensive pharmacological range, including anti-inflammatory, anti-microbials, anti-platelet, and antioxidant activities. [24][25][26][27] The anti-tumor effects of XAG have also been recognized against huamn maliganacies, and it mainly acts via the inhibition of cell proliferation, migration, invasion, and angiogenesis, as well as induction of apoptosis. [28][29][30] In contrast to the findings of Akihisa et al, 31 we found no cytotoxic effect of XAG on HCC cells.…”
Section: Discussionmentioning
confidence: 99%